Introduction (2002)
We have a profession which is informed by established practice…That practice is challenged by theory and also by the experiences of many practitioners. We must take these challenges seriously. One thing is sure. If teachers are to be able to offer their learners a range of language learning activities, if they want to find out how best to meet the needs of their students, if they are to take full advantage of a range of teaching materials and to keep abreast of new teaching opportunities, then they need to adapt to new values, new approaches to language, to learning and to students. They need to assimilate a range of new techniques and procedures. They need to be prepared to experiment and innovate.”